2018
DOI: 10.1002/arch.21504
|View full text |Cite
|
Sign up to set email alerts
|

Development of a highly accurate and sensitive diagnostic tool for pyrethroid‐resistant chimeric P450 CYP337B3 of Helicoverpa armigera using loop‐mediated isothermal amplification

Abstract: Recent studies have shown that pyrethroid resistance in the cotton bollworm (CBW) Helicoverpa armigera is conferred by the generation of a chimeric CYP337B3 gene, which resulted from unequal crossing-over between the CYP337B1 and CYP337B2 genes. In this study, we developed a diagnostic protocol based on the loop-mediated isothermal amplification (LAMP) assay for the detection of chimeric CYP337B3. The CYP337B3 LAMP assay utilized six primers and generated strong fluorescence signals visible to the naked eye un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…As previously reported, the amount of DNA is generally not the limiting factor for the LAMP assay (Choi et al, 2018). Varying the incubation time can generally compensate for different amounts of DNA.…”
Section: Disscussionmentioning
confidence: 81%
See 1 more Smart Citation
“…As previously reported, the amount of DNA is generally not the limiting factor for the LAMP assay (Choi et al, 2018). Varying the incubation time can generally compensate for different amounts of DNA.…”
Section: Disscussionmentioning
confidence: 81%
“…In another attempt to decrease the incubation time, we applied two other loop primers, loop forward (LF) between the F2 and F1 regions and loop backward (LB) between the B1 and B2 regions, which have been suggested to amplify additionally from the loops in the dumbbell forms (Choi et al, 2018). Finding suitable loop primers was difficult because of the high AT content, and the strategy of adding overhanging 'G's to the 5' end to increase the melting temperature was hard to use in the inner primers.…”
Section: Disscussionmentioning
confidence: 99%
“…As previously reported, the amount of DNA is generally not the limiting factor in the LAMP assay. 20 Incubation temperature is more important for specificity. At temperatures below 59°C, M. separata produced false positives with four primers in this study (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…A simpler technique, loopmediated isothermal amplification (LAMP) is widely used for the rapid identification of pest species. [17][18][19][20] It is performed under isothermal conditions that require a set of four primers, a stranddisplacing DNA polymerase, and a water bath or heat block to maintain the temperature at about 60-65°C following one-time denaturation at 95°C or one-step incubation. 21,22 There are no additional steps.…”
Section: Introductionmentioning
confidence: 99%
“…In total, eight CYP337B3 alleles are known worldwide. Among them, two alleles (CYP337B3v2 and v7) were identified and we developed a highly accurate and sensitive diagnostic tool for pyrethroid-resistant chimeric P450 CYP337B3 of H. armigera using loop-mediated isothermal amplification (Choi et al 2018). Recently the genome of H. armigera was sequenced and annotated (Pearce et al 2017).…”
Section: Lepidopteran Pests In Korean Cornfieldsmentioning
confidence: 99%